Fundamental Approaches to Software Engineering : 18th International Conference, FASE 2015, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2015, London, UK, April 11-18, 2015, Proceedings - Egyed, Alexander; Schaefer, Ina.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the proceedings of the 18th International Conference on Fundamental Approaches to Software Engineering, FASE 2015, held in London, UK, in April 2015, as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2015. The 22 full papers and 1 short paper presented in this volume were carefully reviewed and selected from 80 submissions. They are organized in topical sections named: models and synthesis; testing and fault localization; modeling; verification; modeling and adaptation; and applications.
Models and Synthesis -- An Institution for Simple UML State Machines -- Map-Based Transparent Persistence for Very Large Models -- Composing Message Translators and Inferring Their Data Types Using Tree Automata -- On-the-Fly Synthesis of Scarcely Synchronizing Distributed Controllers from Scenario-Based Specifications -- Testing and Fault Localization -- BPEL Integration Testing -- Facilitating Reuse in Multi-goal Test-Suite Generation for Software Product Lines -- Just Test What You Cannot Verify! -- Evaluation of Measures for Statistical Fault Localisation and an Optimising Scheme -- Modeling -- A Generalized Formal Framework for Partial Modeling -- Performance-Based Software Model Refactoring in Fuzzy Contexts -- Analyzing Conflicts and Dependencies of Rule-Based Transformations in Henshin -- Verification -- Translation Validation for Clock Transformations in a Synchronous Compiler -- Symbolic Detection of Assertion Dependencies for Bounded Model Checking -- Verification of Loop -- Parallelisations -- Model-Based Formal Reasoning about Data-Management Applications -- Modeling and Adaptation -- Self-adaptive Software with Decentralised Control Loops -- Model-Based Adaptation of Software Communicating via FIFO Buffers -- Lazy TSO Reachability -- A Variability-Based Approach to Reusable and Efficient Model Transformations -- Applications -- Exploring Scenario Exploration -- Data-Oriented Characterization of Application-Level Energy Optimization -- Resource Specification for Prototyping Human-Intensive Systems -- The Prophecy of Undo.
Keywords: Software engineering; Computer science; Logic design; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Mathematical Logic and Formal Languages